Exceptives and cardinality - Trinh, Tue (Proceedings of Sinn und Bedeutung, 2024)
There are two schools of thoughts on exceptives. The “Fintelians” take exceptives to be modifiers of the NP argument of the determiner, while the “Anti-Fintelians” take them to be something else. I present the observation that exceptives do not tolerate cardinal determiners. I then discuss the problem it poses for two Anti-Fintelian analyses and propose a Fintelian account. The main idea of the account is that exceptives introduce subdomain alternatives.